2010
DOI: 10.1029/2010jd014114
|View full text |Cite
|
Sign up to set email alerts
|

Case studies of the mesospheric response to recent minor, major, and extended stratospheric warmings

Abstract: [1] We have studied the mesospheric response to two recent stratospheric warmings by performing short-term forecasts at medium (1.5°) and high (0.5°) spatial resolution under different gravity wave drag (GWD) scenarios. We validated our models with our highaltitude analysis that extends from 0 to 90 km. For the minor warming of January 2008, reduced upper-level orographic GWD weakened the downward residual circulation and cooled the mesosphere. Parameterized nonorographic GWD increased the simulated mesospheri… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

21
195
0

Year Published

2011
2011
2018
2018

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 136 publications
(219 citation statements)
references
References 61 publications
(143 reference statements)
21
195
0
Order By: Relevance
“…Also the mesosphere (e.g., Labitzke, 1972;Jacobi et al, 2003;Siskind et al, 2005Siskind et al, , 2010Hoffmann et al, 2007;Yamashita et al, 2013;Zülicke and Becker, 2013), and even the thermosphere/ionosphere are affected (e.g., Goncharenko and Zhang, 2008;Fuller-Rowell et al, 2010;Yigit et al, 2014). The selective filtering of gravity waves by the anomalous winds during (major) SSWs is an important mechanism in these vertical influences.…”
Section: Effects Of Gravity Waves During Sswsmentioning
confidence: 99%
“…Also the mesosphere (e.g., Labitzke, 1972;Jacobi et al, 2003;Siskind et al, 2005Siskind et al, , 2010Hoffmann et al, 2007;Yamashita et al, 2013;Zülicke and Becker, 2013), and even the thermosphere/ionosphere are affected (e.g., Goncharenko and Zhang, 2008;Fuller-Rowell et al, 2010;Yigit et al, 2014). The selective filtering of gravity waves by the anomalous winds during (major) SSWs is an important mechanism in these vertical influences.…”
Section: Effects Of Gravity Waves During Sswsmentioning
confidence: 99%
“…In the Modern Era Retrospective-reanalysis for Research and Applications (MERRA) (Reinecker et al 2011) native resolution product, the zonal average zonal balanced winds above 65 km at 69°S showed a pronounced reduction coincident with the July-August stratospheric warming (not shown). Siskind et al (2010), has shown in a model study that mesospheric cooling and zonal wind reduction accompanying stratospheric warmings are potentially produced by a reduction of the residual downward circulation in the mesosphere due to stratospheric critical level filtering of orographic gravity waves.…”
Section: Dynamical Activity In Julymentioning
confidence: 99%
“…Smith (1997) found that the first two mechanisms operate, however, the one that dominates depends on how favorable the conditions are in the middle atmosphere for vertical propagation. The third mechanism is well-known for the in situ generation of the quasi-2-day wave (e.g., Ern et al, 2013).…”
Section: Introductionmentioning
confidence: 99%
“…The third mechanism is well-known for the in situ generation of the quasi-2-day wave (e.g., Ern et al, 2013). A model study by Smith (2003) showed that vertical propagation of SPW dominates up to the lower mesosphere while in situ GW-generated SPWs dominate in the upper mesosphere. This result was confirmed by Lieberman et al (2013) using satellite observations.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation